2021
DOI: 10.1002/mp.15103
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of airway dimensions using a high‐resolution CT scanner: A phantom study

Abstract: Small airways with inner diameters less than 2 mm are sites of major airflow limitations in patients with chronic obstructive pulmonary disease (COPD) and asthma. The purpose of this study is to investigate the limitations for accurate assessment of small airway dimensions using both high-resolution CT (HRCT) and conventional normal-resolution CT at low dose levels. Methods:To model the normal human airways from the 3rd to 20th generations, a cylindrical polyurethane phantom with 14 airway tubes of inner diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…In the current study, for PCD-CT–derived nodule volume measurements at the dose level studied (0.8 mGy), volume accuracy was consistent or improved compared with Zhou et al 19 potentially due to the differences in the PCD-CT scanner platform, acquisition parameters, dose, and reconstruction including kernels, matrix size, and slice thickness. The study by Zhao et al 14 cited nearly a factor of 3 improvement of airway wall thickness measurement accuracy (RMSE) between standard and high-resolution EID-CT images with CTDI vol of 6.2 mGy. In the current study, the RMSEs of the airway tubes similar in size to those used Zhao et al in MK PCD-CT and USK PCD-CT images (CTDI vol = 7.35 mGy) were 0.43 mm and 0.11 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, for PCD-CT–derived nodule volume measurements at the dose level studied (0.8 mGy), volume accuracy was consistent or improved compared with Zhou et al 19 potentially due to the differences in the PCD-CT scanner platform, acquisition parameters, dose, and reconstruction including kernels, matrix size, and slice thickness. The study by Zhao et al 14 cited nearly a factor of 3 improvement of airway wall thickness measurement accuracy (RMSE) between standard and high-resolution EID-CT images with CTDI vol of 6.2 mGy. In the current study, the RMSEs of the airway tubes similar in size to those used Zhao et al in MK PCD-CT and USK PCD-CT images (CTDI vol = 7.35 mGy) were 0.43 mm and 0.11 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning reconstruction methods have been applied to chest CT and pulmonary nodule detection, 13 aiding in noise reduction. High-resolution CT has been used to measure the dimensions of small structures such as airways for the purpose of monitoring for COPD and asthma 4,14 …”
mentioning
confidence: 99%
“…The calculation method was shown in ( 15 ). In ( 16 ), the segmentation effect of the overall segmentation algorithm was measured by the average voxel error [ 21 ]. …”
Section: Methodsmentioning
confidence: 99%
“…65 In addition, high-resolution CT has been used to measure the dimensions of small structures such as airways for the purpose of monitoring for chronic obstructive pulmonary disease and asthma. 66,67 High-resolution PCD-CT has been shown to improve nodule volume quantification, shape characterization, and image quality compared with standard-resolution PCD-CT. 54,58,68,69 Photon-counting detector CT has been applied to nodule volume, emphysema, and airway quantification. [69][70][71][72] In the context of interstitial lung disease, PCD-CT technology maintained diagnostic performance at reduced dose compared with EID-CT. 73,74 Dunning et al 75 showed that PCD-CT improved nodule volume estimation (volume quantification error reduced Gadobutrol (Gadavist; Bayer Healthcare, NJ) contrast agent was first injected intravascularly, followed by an iohexol (Omnipaque 350; GE Healthcare, WI) injection 17.5 seconds from the initial injection.…”
Section: Lungsmentioning
confidence: 99%
“…Lung cancer CT screening is used to detect lung nodules, and estimate of their volumes are used clinically to assess the need for follow-up and/or to monitor nodule growth 65 . In addition, high-resolution CT has been used to measure the dimensions of small structures such as airways for the purpose of monitoring for chronic obstructive pulmonary disease and asthma 66,67 …”
Section: Pcd-ct Improves Spatial Resolution and Geometric Quantificat...mentioning
confidence: 99%